2004
DOI: 10.1523/jneurosci.1063-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Each S Cone in Macaque Fovea Drives One Narrow-Field and Several Wide-Field Blue-Yellow Ganglion Cells

Abstract: A rule of retinal wiring is that many receptors converge onto fewer bipolar cells and still fewer ganglion cells. However, for each S cone in macaque fovea, there are two S-cone ON bipolar cells and two blue-yellow (BY) ganglion cells. To understand this apparent rule reversal, we reconstructed synaptic patterns of divergence and convergence and determined the basic three-tiered unit of connectivity that repeats across the retina. Each foveal S cone diverges to four S-cone ON bipolar cells but contacts them un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…Second, individual blue-cone bipolar cells contact between one and five S-cone pedicles (convergence), whereas S-cone pedicles are contacted by the dendrites of one to five blue-cone bipolar cells (divergence). Third, the density ratio of blue-cone bipolar cells to blue cones is between one and two in the primate Marshak, 1992, 1997;Wässle et al, 1994;Schein et al, 2004) and 1.17 in the mouse retina (Fig. 3).…”
Section: Discussionmentioning
confidence: 95%
“…Second, individual blue-cone bipolar cells contact between one and five S-cone pedicles (convergence), whereas S-cone pedicles are contacted by the dendrites of one to five blue-cone bipolar cells (divergence). Third, the density ratio of blue-cone bipolar cells to blue cones is between one and two in the primate Marshak, 1992, 1997;Wässle et al, 1994;Schein et al, 2004) and 1.17 in the mouse retina (Fig. 3).…”
Section: Discussionmentioning
confidence: 95%
“…bipolar cell signals. Instead, the data suggested that horizontal cells provide the (LϩM)-OFF surround (Dacey, 2000;Herr et al, 2003;Schein et al, 2004). The receptive fields of SBCs formed nonrandom mosaics with overlap and regularity similar to those of ON-parasol cells.…”
Section: Overlapmentioning
confidence: 88%
“…These results indicate that OFF-bipolar cells provide little if any functional input to SBCs in the present conditions. In the discussion, it is proposed that SBCs receive dominant LϩM cone input via H2 horizontal cell feedback (Dacey, 2000;Herr et al, 2003;Schein et al, 2004).…”
Section: The (L؉m)-off Surround Is Eliminated By L-apbmentioning
confidence: 99%
“…In primates and mice, the density ratio of blue cone bipolar cells to blue cones is approximately 1:2 and each blue cone is contacted by more than one blue cone bipolar cell (Kouyama and Marshak, 1992;Kouyama and Marshak, 1997;Schein et al, 2004;Haverkamp et al, 2005). In rabbits, the divergence of blue cone input onto each wide-field bipolar cell depends on retinal eccentricity.…”
Section: Discussionmentioning
confidence: 99%